Classroom behavior, contexts, and interventions - Cook, Bryan G.; Tankersley, Melody; Landrum, Timothy J. (Bingley, U.K. : Emerald, 2012)
The focus of this volume is to identify and review issues and outcomes associated with behavioral concerns of students with learning and behavioral disabilities. Students must navigate a number of environmental conditions, task demands, and social interactions with peers and adults throughout the school day. To be successful, they must employ a variety of learning and self-regulatory strategies, as well as meet teachers expectations in the classroom. Students with learning and behavioral disabilities are more likely to fail in navigating the school day than nondisabled peers. Their failure is often associated with difficulties in some aspect of behavior. In this volume, internationally prominent scholars address contemporary topics such as grade retention, bullying and Harassment, response-to-intervention and universal systems in relation to how students with learning and behavioral disabilities are affected by them. Additionally, the scholars describe and discuss future directions for treatments such as social skills instruction, cognitive-behavioral prevention, social emotional learning programs, and self-monitoring. The volume is intended to be of interest to clinicians, teachers, researchers, graduate students, and others who work with students with learning and behavioral disabilities.
Classroom behavior, context, and interventions : the search for solutions to complex problems / Melody Tankersley, Timothy J. Landrum, Bryan G. Cook -- Targets of self-monitoring : productivity, accuracy, and attention / Andrew Bruce, John Wills Lloyd, Michael J. Kennedy -- Issues related to identifying and implementing evidence-based social skills interventions for students with high-incidence disabilities / Frank M. Gresham, Natalie Robichaux, Haley York, Kristen OLeary -- Cognitive-behavioral interventions to prevent aggression of students with emotional and behavioral disorders / Stephen W. Smith, Gregory G. Taylor, Tia Barnes, Ann P. Daunic -- Attention deficit hyperactivity disorder and academics / Robert Reid -- Teacher expectations for student performance : lessons learned and implications for research and practice / Kathleen Lynne Lane, Erik W. Carter, Eric Common, Adam Jordan -- Adolescent development for students with learning disabilities and behavioral disorders : the promise of social emotional learning / Allison B. Dymnicki, Kimberly T. Kendziora, David M. Osher -- Beyond grade retention and social promotion : toward supporting students with learning and behavioral disabilities / Shane R. Jimerson, Aaron Haddock, Jacqueline A. Brown -- Universal systems for preventing behavior problems / Terrance M. Scott -- Preventing and responding to bullying and harassment in schools : what we know and what can be done / Jeffrey Sprague, Vicki Nishioka -- Preparing teachers to effectively deliver reading instruction and behavioral supports in response to intervention frameworks / Mary T. Brownell, Alexandra Lauterbach, Amber Benedict, Jenna Kimerling, Elizabeth Bettini, Kristin Murphy -- Teachers' causal attributions for student problem behavior : implications for school-based behavioral interventions and research / Andrew L. Wiley, Melody Tankersley, Andrea Simms -- Treatment integrity in intervention research : models, measures, and future directions / Carl J. Liaupsin, Jolenea B. Ferro, John Umbreit.
Keywords: Education -- Special Education -- Learning Disabilities; Education -- Special Education -- Social Disabilities; Education -- Classroom Management; Teaching of specific groups & persons with special educational needs; Teaching of students with specific learning difficulties -- needs; Classroom management; Behavior disorders in children